Service Quality in Community Health Centre - Dr. Kavita A. Jain; Savita (International Journal of Engineering and Management Research, 2022)
The present study has been conducted to understand the level of awareness of people toward quality of services available at CHC level. In order to achieve the objective of this research work, the researcher applied SERVQUAL model through five factors such as Tangibility, Assurance, Responsiveness, Reliability and Empathy. In this way, primary data have been collected from 25 patients at Madina CHC. Further, the collected data have been analysed with the help of Likert five point scale and other statistical tools and techniques. The results of this study suggested that CHC administration should make some more efforts to improve the service quality in terms of Empathy and Reliability.